Immigrants’ access to health care: Problems identified in a high-risk tuberculosis population - R. Linhas; O. Oliveira; P. Meireles; P. Oliveira; M.B. de Melo; J. Lourenço; F. Ferreira; R. Gaio; R. Duarte (Pulmonology)
Introduction Immigrants may utilize health care services differently than other residents and may also have a greater risk for tuberculosis (TB).Objective Identify barriers to healthcare access by immigrants, factors associated with these barriers, and discuss strategies that may reduce these barriers.Material and methods Anonymous questionnaires were given to immigrants at National Immigrant Support Centres between 2015 and 2016. Barriers to healthcare were identified using logistic regression.Results One-hundred and nineteen questionnaires were administered to immigrants, 9 of whom (8%) presented with TB while in Portugal. Twenty-one percent of immigrants reported barriers to healthcare access, and 69% had general practitioners (GPs). The presence of barriers to healthcare access was negatively associated with having a GP and with being married or in a de facto union.Conclusions A considerable proportion of immigrants reported having difficulties accessing healthcare services in Portugal where legally these barriers are nonexistent. Certain factors were associated with these difficulties.